Robust-Set Covering Problem and Sensitivity Analysis to Determine The Location of Temporary Waste Disposal Sites - Octarina, Sisca; Bangun, Putra Bahtera Jaya; Cahyono, Endro Setyo; Suprihatin, Bambang; Sarjani, Ita; Puspita, Fitri Maya; Yuliza, Evi (Science and Technology Indonesia, 2024)
The increasing population has resulted in a significant increase in the amount of waste. One effort that can be made to overcome the waste problem is to provide a Temporary Waste Disposal Site (TWDS). This research aims to optimize the TWDS in the Bukit Kecil sub-district, Palembang city, by formulating a Robust-Set Covering Problem (Robust-SCP) model and solving the model with the software. Sensitivity analysis is used to analyze the optimal solution. Bukit Kecil sub-district is the sub-district that has the highest number of TWDS in Palembang city. The robust-SCP model obtained 10 optimal TWDS. Therefore, this research recommends the Robust SCP model as the optimal solution for the determination of TWDS in the Bukit Kecil sub-district, namely TWDS Kartini Street, TWDS front of Starbucks KI Street, TWDS Merdeka Street, TWDS Illegal at 26 Ilir Market, TWDS Flat Block 35, TWDS Flat Block 49, TWDS Merdeka Women’s Prison, TWDS Musi Riverbank Park, TWDS Monpera, and TWDS Cinde Market, with the addition of TWDS Mayor’s Office in 22 Ilir village and TWDS Flat Block 01 in 23 Ilir village. The sensitivity analysis results in this study show that the solution remains optimal if the coefficient change is within the coefficient interval value.